A 25-Year-Old Sample Contributes the Complete Genome Sequence of Avian Coronavirus Vaccine Strain ArkDPI, Reisolated from Commercial Broilers in the United States - Goraichuk, Iryna V. (Microbiol Resour Announc, 2020)
Here, we report the complete genome sequence of Avian coronavirus strain ArkDPI of the GI-9 lineage, isolated from broiler chickens in North Georgia in 1994. This is the complete genome sequence of this vaccine strain, reisolated from broilers in the United States.